Hard carbon material, secondary battery and electric equipment
By designing the irregular surface sphere structure of hard carbon materials, its surface area and gram capacity are improved, and the problem of low gram capacity of hard carbon materials in secondary batteries is solved, achieving higher energy density and first-time Coulomb efficiency.
Patent Information
- Application Number
- CN202411797078.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The current low g capacity of hard carbon materials limits its application potential in secondary batteries, and is especially unable to be directly used in sodium ion batteries.
Provide a hard carbon material with irregular surface spherical structure, with characteristic parameters of 0≤a/D≤0.5 and 0.04≤b/D≤0.55. Through this structure, the particle surface area is increased and the active ion contact site is increased. , thereby increasing the capacity of gram.
By increasing the surface area of hard carbon materials, the active ion storage capacity in secondary batteries is improved, and the capacity and energy density are significantly improved.
Smart Images

Figure CN119275286A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a hard carbon material, a secondary battery and an electrical device. Background Art
[0002] Secondary batteries are being promoted and applied due to their advantages such as high energy density, low self-discharge rate, and good cycle performance. The common negative electrode material of secondary batteries is graphite, but because it can only be used in lithium-ion batteries and cannot be directly applied to sodium-ion batteries, its application scenarios are relatively limited. Since hard carbon materials can be used as negative electrode materials in both lithium-ion batteries and sodium-ion batteries, they have broader application prospects. However, the current gram capacity of hard carbon materials still needs to be improved. Summary of the invention
[0003] The present application provides a hard carbon material, a secondary battery and an electrical device, which are used to improve the first coulombic efficiency and energy density of the secondary battery in which the hard carbon material is located by providing a hard carbon material with a high gram capacity.
[0004] In a first aspect, an embodiment of the present application provides a hard carbon material, the hard carbon material comprising: a spheroid having an irregular surface; wherein 0≤a / D≤0.5, 0.04≤b / D≤0.55, a is the depth of the irregular surface, b is the length of a line segment whose endpoint is located at the edge of the vertical projection of the irregular surface, passes through the geometric center of the vertical projection, and is perpendicular to the longest line segment on the vertical projection, the longest line segment on the vertical projection is the longest line segment whose endpoint is located at the edge of the vertical projection and passes through the geometric center of the vertical projection, D is the length of the longest line segment whose endpoints are located on the surface of the spheroid and passes through the geometric center of the spheroid.
[0005] In one embodiment, b ≥ 1.41 μm.
[0006] In one embodiment, b ≥ 2.41 μm.
[0007] In one embodiment, b ≥ 3.76 μm.
[0008] In one embodiment, b<10 μm.
[0009] In one embodiment, the hard carbon material is a spheroid with irregular surfaces.
[0010] In one embodiment, 0≤a / b≤3.75.
[0011] In one embodiment, the hard carbon material satisfies at least one of the following conditions: (1) 0.13 ≤ a / D ≤ 0.47; (2) b / D ≥ 0.08; (3) 0.39 ≤ a / b ≤ 2.35.
[0012] In one embodiment, 0.13 ≤ a / D ≤ 0.47.
[0013] In one embodiment, b / D ≥ 0.08.
[0014] In one embodiment, 0.39 ≤ a / b ≤ 2.35.
[0015] In one embodiment, 0.13 ≤ a / D ≤ 0.47, b / D ≥ 0.08, 0.39 ≤ a / b ≤ 2.35.
[0016] In one embodiment, in the SEM image at a magnification of 5000X, in at least one region of (20 ± 0.1) μm × (20 ± 0.1) μm, c / N ≥ 0.3; c is the number of the spheroid-like bodies having the irregular surface in the region, and N is the number of the particles of the hard carbon material in the region.
[0017] In one embodiment, in the SEM image at a magnification of 5000X, in at least one region of (20 ± 0.1) μm × (20 ± 0.1) μm, 0.8 < n / N < 5.1, where n is the total number of the irregular surfaces in the region, and N is the number of the particles of the hard carbon material in the region.
[0018] In one embodiment, the tap density of the hard carbon material is 0.88 to 1.12 g / cm 3 .
[0019] In one embodiment, D v 50 is 1.6 to 18.0 μm, D v 90 is 4.2 to 35.0 μm.
[0020] In one embodiment, the tap density of the hard carbon material is 0.90 to 1.02 g / cm 3 .
[0021] Second, the embodiments of the present application provide a secondary battery, including a positive electrode sheet, a negative electrode sheet, and an electrolyte. The negative electrode sheet includes a current collector and a negative electrode material attached to at least one surface of the current collector. Among them, the negative electrode material includes the hard carbon material according to the first aspect and any possible embodiment thereof.
[0022] Third, the embodiments of the present application provide an electrical device, including: The secondary battery described in the second aspect.
[0023] One or more technical solutions provided in the embodiments of the present application have at least the following beneficial effects: The embodiment of the present application increases the surface area of the hard carbon material by using the properties of spheroids with irregular surfaces in the hard carbon material satisfying 0≤a / D≤0.5, 0.04≤b / D≤0.55, so that when it is used as a negative electrode material for a secondary battery, the active ions (for example, Li + 、Na + ) increases the probability of contact with the hard carbon material, causing the active ions to be stored in the hard carbon material and increasing the gram capacity of the hard carbon material.
[0024] Other features and advantages of the present application will be described in the subsequent description, and partly become apparent from the description, or be understood by practicing the present application. The purposes and other advantages of the present application can be realized and obtained by the structures specifically pointed out in the written description, claims, and drawings. It should be understood that the above general description and the detailed description below are only exemplary and explanatory and cannot limit the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0026] Figure 1A A schematic diagram of the structure of a hard carbon material provided in an embodiment of the present application; Figure 1B A schematic diagram of an irregular surface of a hard carbon material provided in an embodiment of the present application; Figure 2 This is a SEM schematic diagram of a hard carbon material provided in an embodiment of the present application. DETAILED DESCRIPTION
[0027] In view of the problem of low gram capacity of current hard carbon materials, an embodiment of the present application provides a hard carbon material, the hard carbon material includes a spheroid with an irregular surface, in which the ratio a / D of the depth a of the irregular surface to the length D of the longest line segment connecting two points on the surface of the spheroid and passing through its geometric center satisfies: 0≤a / D≤0.5; And, the ratio b / D of the length b of a line segment whose endpoint is located at the edge of the vertical projection of the irregular surface, passes through the geometric center of the vertical projection, and is perpendicular to the longest line segment on the vertical projection to the above-mentioned D satisfies: 0.04≤b / D≤0.55.
[0028] It can be seen that the hard carbon material has the advantage of a large particle surface area. Therefore, when it is used in secondary batteries, this property can enable the hard carbon material to provide more contact sites for active ions (for example, sodium ions, lithium ions), thereby increasing the gram capacity of the hard carbon material.
[0029] To make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0030] The terms “first” and “second” in the specification and claims of this application and the above drawings are used to distinguish different objects rather than to describe a specific order.
[0031] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0032] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0033] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0034] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0035] The present application embodiment first provides a hard carbon material, which includes: a spheroid with irregular surfaces. The spheroid with irregular surfaces has the following geometric features, please refer to Figure 1A-1B : 0≤a / D≤0.5, 0.04≤b / D≤0.55.
[0036] Wherein, a is the depth of the above irregular surface, unit: μm.
[0037] b is the length of the line segment whose endpoint is located at the edge of the vertical projection of the irregular surface, passing through the geometric center of the vertical projection and perpendicular to the first longest line segment on the vertical projection. Please refer to Figure 1B , unit: μm.
[0038] The longest line segment on the vertical projection is the longest line segment whose endpoint is located at the edge of the vertical projection and passes through the geometric center of the vertical projection. The size parameters of the vertical projection and the edge profile of the irregular surface are equal.
[0039] D is the length of the longest line segment whose endpoint is located on the surface of the spheroid and passes through the geometric center of the spheroid, in μm.
[0040] The particle surface of the same hard carbon material may include one or more irregular surfaces, please refer to Figure 2 .
[0041] The irregular surface may include a curved surface and / or a flat surface.
[0042] Among them, irregular surfaces including curved surfaces are surfaces whose curvature is different from that of most positions of the spherical surface, and specifically may be concave surfaces or convex surfaces.
[0043] The plane may be one or more surfaces extending in different directions, for example, it may form an outwardly protruding angular surface, or an inwardly concave angular surface.
[0044] In the above-mentioned irregular surface of the spheroidal surface, b≥1.41μm. When the irregular surface of the spheroidal surface satisfies b≥1.41μm, the gram capacity of the hard carbon particles can be further improved. Exemplarily, the value of b can be 1.41, 1.91, 2.41, 2.90, 2.97, 3.20, 3.50, 3.70, 3.90, 4.10, 4.20, 4.50, 4.90, 5.30, 5.80, 6.20, 6.70, 7.20, 7.80, 8.20, 8.60, 9.00, 9.50, 9.99 or a range consisting of any two values thereof. Preferably b≥2.41μm. Or preferably b≥3.76μm.
[0045] In one embodiment, b<10 μm.
[0046] Furthermore, the above-mentioned hard carbon materials are all spherical bodies with irregular surfaces.
[0047] The hard carbon material may be a primary particle. The primary particle may include a spheroid with irregular surfaces, an ellipsoid and / or a sphere. Alternatively, the primary particles are all spheroids with irregular surfaces.
[0048] Accordingly, when the hard carbon material is a secondary particle, the secondary particle may include a spheroid with irregular surfaces, an ellipsoid and / or a sphere. Alternatively, the secondary particles are all spheroids with irregular surfaces.
[0049] Exemplarily, the value of the ratio a / D of the depth a of the irregular surface to the length D of the longest line segment connecting two points on the surface of the spheroid and passing through the geometric center thereof may be 0.00, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50 or a range consisting of any two of these values; The value of the ratio b / D of the above-mentioned b to the above-mentioned D can be 0.04, 0.09, 0.14, 0.19, 0.24, 0.27, 0.33, 0.39, 0.44, 0.49, 0.55 or a range consisting of any two values therein.
[0050] To further increase the gram capacity of the hard carbon material, in one embodiment, 0.13≤a / D≤0.47, b / D≥0.08. For example, the value of a / D can be 0.13, 0.16, 0.19, 0.22, 0.24, 0.26, 0.28, 0.29, 032, 0.35, 0.38, 0.41, 0.44, 0.47 or a range consisting of any two of the values; Illustratively, the value of b / D may be 0.08, 0.10, 0.12, 0.14, 0.20, 0.22, 0.24, 0.28, 0.30, 0.33, 0.36, 0.40, 0.43, 0.46, 0.50, 0.52, 0.55, or a range consisting of any two of the values.
[0051] In one embodiment, D is 1.68-47.00 μm. Preferably, D ≥ 8.48 μm. Exemplarily, the value of D can be 8.48, 9.50, 10.50, 11.50, 12.50, 13.50, 14.50, 15.50, 16.50, 17.50, 18.50, 19.50, 20.50, 21.50, 22.50, 23.50, 24.50, 25.00, 26.00, 30.00, 33.00, 36.00, 43.00, 47.00 or a range consisting of any two of the values.
[0052] In one embodiment, a≤16.92 μm. Preferably, a≥0.80 μm. For example, the value of a can be 0.80, 0.90, 1.00, 1.20, 1.40, 2.00, 3.00, 4.00, 5.00, 6.00, 7.00, 8.00, 9.00, 10.00, 11.00, 12.00, 13.00, 14.00, 15.00, 16.00, 16.92, or a range consisting of any two of the values.
[0053] In one embodiment, in the spheroid of the above-mentioned specific irregular surface, the ratio a / b of the depth a of the irregular surface and the length b of a line segment whose endpoint is located at the edge of the vertical projection of the irregular surface, passes through the geometric center of the vertical projection, and is perpendicular to the longest line segment on the vertical projection satisfies: 0≤a / b≤3.75.
[0054] Illustratively, the value of a / b may be 0.00, 0.40, 1.00, 1.50, 2.00, 2.50, 3.00, 3.50, 3.75, or a range consisting of any two values thereof.
[0055] To further improve the specific capacity of the hard carbon material, in one embodiment, 0.39 ≤ a / b ≤ 2.35. Exemplarily, the value of a / b can be 0.39, 0.41, 0.45, 0.49, 0.54, 0.59, 0.64, 0.69, 0.74, 0.77, 0.81, 0.82, 0.83, 0.88, 0.94, 0.99, 1.05, 1.08, 1.13, 1.18, 1.23, 1.28, 1.38, 1.40, 1.90, 2.10, 2.15, 2.25, 2.35 or the range formed by any two of these values.
[0056] In one embodiment, in the SEM image at a magnification of 5000X, there is at least one region of (20 ± 0.1) μm × (20 ± 0.1) μm that satisfies: c / N ≥ 0.3; c is the number of spheroids with irregular surfaces in this region, and N is the number of hard carbon material particles in the region.
[0057] Furthermore, in the SEM image at a magnification of 5000X, any region of (20 ± 0.1) μm × (20 ± 0.1) μm satisfies: c / N ≥ 0.3.
[0058] To avoid the problem that the hard carbon material is prone to fragmentation due to the large number of irregular surfaces on the particle surface, and the particles of the hard carbon material are easily squeezed by the edges (i.e., corners) of the irregular surfaces of adjacent particles, resulting in a decrease in the strength of the electrode sheet. In one embodiment, in the SEM image at a magnification of 5000X, there is at least one region of (20 ± 0.1) μm × (20 ± 0.1) μm that satisfies: 0.8 < n / N < 5.1, where n is the total number of irregular surfaces of all types of spheroids in this region, and N is the number of hard carbon material particles in this region.
[0059] Furthermore, in the SEM image at a magnification of 5000X, any region of (20 ± 0.1) μm × (20 ± 0.1) μm satisfies: 0.8 < n / N < 5.1.
[0060] In one embodiment, the tap density of the above-mentioned hard carbon material is 0.88~1.12 g / cm 3 .
[0061] Exemplarily, the tap density of this hard carbon material can be 0.88 g / cm 3 , 0.89 g / cm 3 , 0.90 g / cm 3 , 0.91 g / cm 3 , 0.92 g / cm 3 , 0.93 g / cm 3 , 0.94 g / cm 3 , 0.95 g / cm3 、0.96g / cm 3 , 0.97g / cm 3 、0.98g / cm 3 , 0.99g / cm 3 , 1.00g / cm 3 , 1.01g / cm 3 , 1.05g / cm 3 , 1.10g / cm 3 , 1.12g / cm 3 Or a range consisting of any two values.
[0062] In one embodiment, D v 50 is 1.6~18.0μm, D v 90 is 4.2~35.0μm.
[0063] Among them, D v 50 is the volume median particle size. v 90 refers to the particle size of particles that reach 90% of the volume accumulation from the smaller particle size side in the volume-based particle size distribution. That is, the volume of the negative electrode active material smaller than this particle size accounts for 90% of the total volume of the negative electrode active material.
[0064] For example, D v 50 can be: 1.6μm, 2.0μm, 3.0μm, 4.0μm, 5.0μm, 6.0μm, 7.0μm, 8.0μm, 9.0μm, 10.0μm, 11.0μm, 12.0μm, 13.0μm, 14.0μm, 15.0μm, 18.0μm or a range consisting of any two values therein.
[0065] D v 90 can be 4.2μm, 5.0μm, 8μm, 11μm, 14μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm or a range consisting of any two values therein.
[0066] In one embodiment, 2 μm ≤ (D v 90-D v 50)≤17μm. Preferably, (D v 90-D v 50) ≥10μm.
[0067] Based on the same inventive concept, the present application also provides a method for preparing a hard carbon material, the method comprising the following steps: Step 201: subjecting a hard carbon precursor to a solvothermal reaction to generate a first intermediate material.
[0068] Specifically, the temperature condition of the solvothermal reaction is 180-300°C; for example, it can be 60°C, 100°C, 140°C, 180°C, 250°C or a range consisting of any two values therein.
[0069] The time condition of the solvothermal reaction is 12 to 24 hours.
[0070] The hard carbon precursor includes at least one of a carbon-containing polymer, a pitch-based material, a biomass material, and carbon derived from a biomass material.
[0071] The carbon-containing polymer has carbon as the basic skeleton, and the carbon-containing polymer includes at least one of epoxy resin, phenolic resin, polyol, polyvinyl alcohol and polythiophene.
[0072] The above-mentioned asphalts may include at least one of petroleum asphalt, coal tar asphalt and natural asphalt.
[0073] The biomass material includes at least one of glucose, fructose, sucrose, maltose, starch and tannin.
[0074] The biomass material-derived carbon includes at least one of polymer carbon, biomass carbon and mesophase carbon microbeads.
[0075] Furthermore, the solvent used in the above-mentioned solvothermal reaction includes at least one of water, ethanol, isopropanol, benzene, ethylene glycol and hydrazine hydrate.
[0076] Step 202: Sinter the first intermediate material in an inert atmosphere to obtain a porous carbon material.
[0077] The inert atmosphere may be at least one of nitrogen, argon, and helium.
[0078] The sintering temperature may be 600-1000° C., and the sintering time may be 2-15 hours.
[0079] Step 203, crushing the porous carbon material to obtain a hard carbon material.
[0080] The crushing process can be at least one of air flow crushing, mechanical crushing, or ball mill crushing.
[0081] Air flow crushing is preferred. The conditions for air flow crushing include: air flow pressure of 0.30-0.85 MPa, time of 10-30 min. The air flow velocity can be 9 m / s. 3 / min、10m 3 / min、11m 3 / min、12m 3 / min, etc.
[0082] Based on the same inventive concept, the embodiment of the present application further provides a negative electrode plate, which includes a current collector and a negative electrode material attached to at least one side of the current collector. The negative electrode material includes the hard carbon material as described above.
[0083] Specifically, the current collector may be: aluminum foil, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or a polymer substrate coated with a conductive metal. The conductive metal includes but is not limited to copper, nickel or titanium. The components of the polymer substrate include but are not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate, and poly(p-phenylene terephthalamide).
[0084] In one embodiment, the thickness of the negative electrode current collector is 4-12 μm.
[0085] The thickness of the negative electrode material layer on either side of the negative electrode current collector is 30 to 130 μm.
[0086] In one embodiment, based on the negative electrode material, the mass percentage of the hard carbon material is 10% to 100%.
[0087] The negative electrode material further includes at least one of a thickener, a conductive agent and a binder.
[0088] The thickener may be, for example, sodium carboxymethyl cellulose.
[0089] Conductive agents may include, but are not limited to, carbon materials, metals, or conductive polymers. Carbon materials may include at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon nanofibers, natural graphite, artificial graphite, flake graphite, carbon dots, and graphene. Metals may include at least one of metal powders and metal fibers of copper, iron, aluminum, and the like. Conductive polymers may include at least one of polythiophene, polypyrrole, polyaniline, polyaniline, and polyphenylene vinylene.
[0090] The binder may include, but is not limited to, at least one of polypropylene alcohol, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyamideimide, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl pyrrolidone, polyethylene, polypropylene, epoxy resin, nylon, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral, water-based acrylic resin, carboxymethyl cellulose (CMC) and sodium carboxymethyl cellulose (CMC Na).
[0091] Based on the same inventive concept, an embodiment of the present application further provides a secondary battery, which includes the aforementioned negative electrode plate.
[0092] The secondary battery also includes a positive electrode plate, a separator and an electrolyte.
[0093] The isolation film may be, for example, polypropylene (PP) or polyethylene (PE).
[0094] The positive electrode plate includes a current collector and a positive electrode material disposed on the surface of the current collector on the side opposite to the negative electrode plate. The current collector can be aluminum foil, aluminum foam, aluminum composite current collector (i.e., a current collector with a polymer support layer in the middle and aluminum metal layers on both sides), nickel foil, or nickel foam.
[0095] In one embodiment, the secondary battery is a lithium-ion battery; the positive electrode material is a lithium-ion positive electrode material, such as lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, Prussian blue, etc.
[0096] The aforementioned electrolyte includes a lithium salt and a non-aqueous solvent.
[0097] Among them, the lithium salt includes at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, C4BLiO8, LiBO2 and BF2H2LiO.
[0098] The non-aqueous solvent may include, but is not limited to, carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0099] In one embodiment, the secondary battery is a sodium ion battery, and the positive electrode material may be, for example, Prussian white.
[0100] The electrolyte includes a sodium salt and a non-aqueous solvent. The sodium salt may include at least one of NaPF6, NaClO4, NaBCl4, NaSO3CF3 and Na(CH3)C6H4SO3.
[0101] The non-aqueous solvent includes, but is not limited to, carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0102] In one embodiment, the carboxylate compound in the above-mentioned non-aqueous solvent may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid, valerolactone and caprolactone.
[0103] In one embodiment, the ether compound in the above non-aqueous solvent may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran and tetrahydrofuran.
[0104] In one embodiment, other organic solvents in the above-mentioned non-aqueous solvent may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0105] In one embodiment, the carbonate compound in the non-aqueous solvent may include, but is not limited to, at least one of a linear carbonate compound, a cyclic carbonate compound, and a fluorinated carbonate compound.
[0106] The linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) and ethyl methyl carbonate (MEC).
[0107] The cyclic carbonate may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) and vinyl ethylene carbonate (VEC).
[0108] The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, and trifluoromethylethylene carbonate.
[0109] Based on the same inventive concept, an embodiment of the present application also provides an electrical device.
[0110] The electrical equipment includes, but is not limited to, laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0111] The following is described in detail by examples and comparative examples: The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0112] 1. Test methods and equipment (1) Based on the SEM images, various parameters of spherical bodies with irregular surfaces in hard carbon materials were tested.
[0113] Among the multiple SEM images of hard carbon particles taken at a magnification of 5000X, first, 10 hard carbon particles with complete morphology are randomly selected.
[0114] Then, the three-dimensional morphology images of the hard carbon particles are fitted respectively, and the geometric center of the hard carbon particles is determined in the three-dimensional morphology images; the length of the longest line segment whose endpoint is located on the surface of the three-dimensional morphology image and passes through its geometric center is taken as the first target value; the average value of the first target values of the above-mentioned 10 hard carbon particles is calculated to obtain D.
[0115] For the irregular surfaces of the 10 hard carbon particles mentioned above, b is measured: the vertical projections of the irregular surfaces of the hard carbon particles are fitted respectively to determine the geometric center of the vertical projection; the longest line segment passing through the geometric center of the vertical projection and with its endpoint located at the edge of the vertical projection is determined as the longest line segment on the vertical projection; the length of the line segment with its endpoint located at the edge of the vertical projection, passing through the geometric center of the vertical projection, and perpendicular to the longest line segment on the vertical projection is determined as the second target value; the second target value is the second target value of the irregular surface. The average of the second target values of the irregular surfaces on the hard carbon particles is calculated to obtain b.
[0116] It should be noted that in order to avoid the problem of excessive error in b caused by large vertical projection error when measuring b on the irregular surface of the side of the hard carbon particle using the above method, when measuring b in the embodiment of the present application, an irregular surface with clear edges and located below the SEM shooting field of view (i.e., facing the SEM electron microscope lens) is selected.
[0117] By using image processing software, the depth of the irregular surface on the hard carbon particles is measured respectively, and the average value is calculated to obtain a. The depth can be measured in the following way: First, fit the three-dimensional image of the irregular surface. Determine the two points on the edge of the irregular surface that are farthest apart, and select any one of the two points as the reference point, and determine the target point on the edge of the irregular surface. The distance between the target point and the reference point is 1 / 4 of the circumference of the edge of the irregular surface. Fit the plane where the edge of the irregular surface is located through the two points farthest apart and the target point. Next, in the three-dimensional image of the irregular surface, determine the point on the irregular surface that is farthest from the plane, and record it as the farthest point; then the vertical distance between the farthest point and the plane is the depth.
[0118] Next, in the above SEM image with a magnification of 5000X, select any three (20±0.1)μm×(20±0.1)μm areas, count the number of hard carbon particles in each area, and calculate the average number of hard carbon particles in each of the three areas to obtain N.
[0119] The number of irregular surfaces in each area is counted, and the average number of irregular surfaces in each of the three areas is calculated to obtain n.
[0120] (2) Testing the compaction density of hard carbon materials The compaction density test method is implemented in accordance with GB / T 24533-2009 "Graphite Anode Materials for Lithium-ion Batteries".
[0121] Specifically, 1.0000±0.0500 g of hard carbon material is weighed as a test sample.
[0122] Then, the weighed hard carbon material was placed in a test mold model: CARVER#3619 (13 mm), and then placed together with the test mold in a test device (model: Sansi Zongheng UTM7305) for testing.
[0123] Among them, the test tonnage is 5.0 tons, the pressure increase rate is 10mm / min, the pressure increase holding time is 30s, the pressure relief rate is 30mm / min, and the pressure relief holding time is 10s.
[0124] The compaction density can be measured when the pressure is released. The compaction density D is calculated according to the following formula: ; Wherein, m is the mass of the hard carbon material, S is the force-bearing area of the hard carbon material during the test, and h is the thickness of the hard carbon material during the test.
[0125] (3) Testing the particle size of hard carbon materials The particle size test method here refers to GB / T 19077-2016 "Particle Size Analysis by Laser Diffraction Method".
[0126] Specifically, 1 g of the sample was weighed, mixed evenly with 20 mL of deionized water and a trace amount of dispersant, and then placed in an ultrasonic device for 5 minutes.
[0127] Then, the sonicated solution was poured into the sample injection system Hydro 2000SM for testing. The testing equipment used was Mastersizer 3000 produced by Malvern.
[0128] The refractive index of the particles used in the test was 1.8. Each sample was tested three times, and the particle size test results (Dv10 and Dv90) were the average of the three test results.
[0129] (4) The electrochemical performance of the hard carbon material was tested by testing a secondary battery in which the hard carbon material was used as a component of the negative electrode material.
[0130] ①Preparation of secondary batteries The hard carbon negative electrode material, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) were fully stirred and mixed in deionized water at a mass ratio of 97:2:1 to form a negative electrode slurry with a solid content of 40wt%. The negative electrode slurry was coated on both sides of the negative electrode collector copper foil with a single-side thickness of 60 microns. After drying at 85°C, cold pressing, cutting, and slitting, it was continued to be vacuum dried at 120°C for 12 hours to obtain a negative electrode sheet.
[0131] Preparation of positive electrode D v 50 is 10μm positive electrode active material ternary material (LiNi 0.8 Co 0.1 Mn 0.1 O2), as well as porous carbon additives, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in N-methylpyrrolidone (NMP) solvent in a mass ratio of 96:1:1.4:1.6 to form a positive electrode slurry with a solid content of 72wt%.
[0132] The positive electrode material is coated on the positive electrode current collector aluminum foil, dried at 85° C., and then cold pressed, cut and slit, and dried at 85° C. under vacuum for 4 hours to obtain a positive electrode sheet.
[0133] Preparation of electrolyte In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (PP), and ethyl propionate (EP) were mixed at a mass ratio of EC:PC:EP:PP=25:10:25:40. Then 1,3-propane sultone and fluoroethylene carbonate were added, dissolved and fully stirred, and then lithium salt LiPF6 was added and mixed to obtain an electrolyte, wherein the content of 1,3-propane sultone was 2.5%, the content of fluoroethylene carbonate was 3.6%, and the content of LiPF6 was 12.5%, and all contents refer to the mass content in the electrolyte.
[0134] Preparation of isolation membrane A 7 μm thick polyethylene (PE) porous polymer film was used as the isolation membrane.
[0135] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrodes to play an isolating role. Then, after winding and welding the pole ears, they are placed in an outer packaging foil aluminum-plastic film, and electrolyte is injected. After vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.
[0136] ②Test gram capacity and first coulomb efficiency The negative electrode sheet was cut into a disc with a diameter of 14 mm as the working electrode. The lithium sheet was used as the first effector, the porous polyethylene film was used as the separator, and the button battery was assembled after injecting the electrolyte. The electrolyte includes a base solvent and a lithium salt. The base solvent is obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a mass ratio of 1:1. The lithium salt is LiPF6, and the lithium salt concentration is 1 mol / L.
[0137] The button battery was first discharged to 0V at three stages of low currents of 0.05C, 0.01C, and 0.005C, and the first discharge capacity of the button battery was recorded. Then, it was charged to 2.5V at a constant current of 0.1C, and the first charge capacity of the button battery was recorded.
[0138] The mass of the hard carbon material on the negative electrode sheet is calculated according to the coating mass and area of the slurry during the preparation of the electrode sheet. The first coulomb efficiency is calculated according to the following formula: first coulomb efficiency = first charge capacity / first discharge capacity × 100%.
[0139] The first reversible gram capacity of the hard carbon material from 0V to 2.5V, that is, the total gram capacity after delithiation Q = the first charging capacity / the mass of the hard carbon material, is expressed in mAh / g.
[0140] 0V to 0.1V Li / Li + The gram capacity of the hard carbon material within the potential range is recorded as Q1; 0V to 0.8V Li / Li +The gram capacity of the hard carbon material within the potential range is recorded as Q2.
[0141] ③ Test Energy Density (ED) The soft-pack lithium-ion batteries corresponding to the embodiments and comparative examples were charged to 4.48V at a current of 0.2C at room temperature, and then charged at a constant voltage; then discharged to 2.0V at a constant current of 0.2C, which was recorded as one cycle, and the discharge capacity D and discharge energy E of the first cycle were recorded. The length, width and thickness of the cell at 50% charge were tested, and the volume V of the cell was calculated. The average discharge voltage U=E / D, and the volume energy density was calculated as: VED=(D×U) / V.
[0142] (II) Preparation Example 1 S1. Dissolve 120 g of glucose in 300 mL of deionized water.
[0143] S2. The solution was transferred to a 500 mL hydrothermal kettle and reacted at 180° C. for 12 hours. After the reaction, the solution was cooled, washed, and dried to obtain a dry powder.
[0144] S3. Keep the dried powder at 750° C. in an argon atmosphere for 2 hours, and then cool it down to obtain a carbonized powder.
[0145] S4, air flow crushing the carbonized powder to obtain hard carbon material. The conditions of air flow crushing are: air flow pressure of 0.8Mpa, air flow velocity of 10m 3 / min, processing time is 30min.
[0146] Example 2 The steps and parameters consistent with those in Example 1 were adopted; the only difference was the air flow crushing conditions in step S4: the air flow pressure was 0.8 MPa, the air flow velocity was 10 m / s. 3 / min, the processing time is 20min.
[0147] Example 3 The steps and parameters consistent with those in Example 1 were adopted; the only difference was the air flow crushing conditions in step S4: the air flow pressure was 0.8 MPa, the air flow velocity was 10 m / s. 3 / min, processing time is 15min.
[0148] Example 4 The steps and parameters consistent with those in Example 1 were adopted; the only difference was the air flow crushing conditions in step S4: the air flow pressure was 0.6 MPa, the air flow velocity was 10 m / s. 3 / min, processing time is 15min.
[0149] Example 5 The steps and parameters consistent with those in Example 1 were adopted; the only difference was the air flow crushing conditions in step S4: the air flow pressure was 0.6 MPa, the air flow velocity was 10 m / s. 3 / min, processing time is 10min.
[0150] Example 6 The steps and parameters consistent with those in Example 1 are adopted; the only difference is that the air flow crushing conditions in step S4 are: the air flow pressure is 0.3Mpa, the air flow velocity is 10m 3 / min, processing time is 30min.
[0151] Example 7 The steps and parameters are the same as those in Example 1, except that: In S2, the hydrothermal reactor is set at 200°C for reaction for 24 hours.
[0152] In S4, the air flow crushing conditions are: air flow pressure is 0.3Mpa, air flow velocity is 10m 3 / min, the processing time is 20min.
[0153] Example 8 The steps and parameters are the same as those in Example 1, except that: In S2, the hydrothermal reactor was set at 250°C for reaction for 24 hours.
[0154] In S4, the air flow crushing conditions are: air flow pressure is 0.3Mpa, air flow velocity is 10m 3 / min, processing time is 10min.
[0155] Example 9 The steps and parameters are the same as those in Example 1, except that: In S3, the dried powder is kept at 1000°C for 2 hours in an argon atmosphere and then cooled to obtain a carbonized powder.
[0156] Example 10 The steps and parameters are the same as those in Example 1, except that: In S3, the dried powder is kept at 600°C for 2 hours in an argon atmosphere and then cooled to obtain a carbonized powder.
[0157] Embodiment 11 The steps and parameters are the same as those in Example 1, except that: In S3, the dried powder is kept at 600°C for 1 hour in an argon atmosphere and then cooled to obtain a carbonized powder.
[0158] Example 12 The steps and parameters are the same as those in Example 1, except that: In S3, the dried powder is kept at 600°C in an argon atmosphere for 15 hours and then cooled to obtain a carbonized powder.
[0159] Comparative Example 1 The steps and parameters are the same as those in Example 1, except that: In S4, the air flow crushing conditions are: air flow pressure is 0.85Mpa, air flow velocity is 20m 3 / min, the processing time is 100min.
[0160] Comparative Example 2 The steps and parameters are the same as those in Example 1, except that: In S2, the reaction conditions of the hydrothermal reactor are set to: 300°C, reaction time 24 hours.
[0161] In S4, the air flow crushing conditions are: air flow pressure is 0.2Mpa, air flow velocity is 5m 3 / min, the processing time is 5min.
[0162] For ease of reading, the main parameters in the preparation process of the above hard carbon material are first summarized in Table 1. Among them, T1 is the reaction temperature in the hydrothermal reactor in S2, and t1 is the reaction time in the hydrothermal reactor in S2. T2 is the insulation temperature in the argon atmosphere in S3, and t2 is the insulation time in the argon atmosphere in S3. P is the air flow crushing pressure in S4, v is the air flow velocity in S4, and t3 is the duration of the air flow crushing treatment in S4.
[0163] Table 1
[0164] The test results of the intrinsic properties of the hard carbon materials in the above embodiments and comparative examples are shown in Tables 2 and 3.
[0165] Table 2
[0166] Table 3
[0167] The test data of the electrochemical performance of the hard carbon materials in the above embodiments and comparative examples are shown in Table 4.
[0168] Table 4
[0169] It can be seen that when the spherical bodies with irregular surfaces in the hard carbon material satisfy: 0≤a / D≤0.5, 0.04≤b / D≤0.55, the hard carbon material exhibits a higher gram capacity; at the same time, it also exhibits a higher first coulombic efficiency and energy density.
[0170] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.
Claims
1. A hard carbon material, characterized in that: The hard carbon material includes: spheroids with irregular surfaces; wherein, 0≤a / D≤0.5, 0.04≤b / D≤0.55, a is the depth of the irregular surface, b is the length of a line segment whose endpoints are located at the edges of the vertical projection of the irregular surface, passes through the geometric center of the vertical projection, and is perpendicular to the longest line segment on the vertical projection, and the longest line segment on the vertical projection is the longest line segment whose endpoints are located at the edges of the vertical projection and passes through the geometric center of the vertical projection, D is the length of the longest line segment whose endpoints are located on the surface of the spheroid and passes through the geometric center of the spheroid.
2. The hard carbon material according to claim 1, characterized in that b≥2.41μm.
3. The hard carbon material according to claim 1, characterized in that b≥3.76μm.
4. The hard carbon material according to any one of claims 1 to 3, characterized in that 0≤a / b≤3.
75.
5. The hard carbon material according to claim 1, characterized in that The hard carbon material satisfies at least one of the following conditions: (1) 0.13≤a / D≤0.47; (2) b / D≥0.08; (3) 0.39≤a / b≤2.
35.
6. The hard carbon material according to any one of claims 1 to 3 and 5, characterized in that: In the SEM image at a magnification of 5000X, in at least one region of (20±0.1)μm×(20±0.1)μm, c / N≥0.3; c is the number of spheroids with the irregular surface in the region, and N is the number of particles of the hard carbon material in the region.
7. The hard carbon material according to any one of claims 1 to 3 and 5, characterized in that: In the SEM image at a magnification of 5000X, in at least one region of (20±0.1)μm×(20±0.1)μm, 0.8<n / N<5.1, n is the total number of the irregular surfaces in the region, and N is the number of particles of the hard carbon material in the region.
8. The hard carbon material according to claim 1, characterized in that The compacted density of the hard carbon material is 0.88-1.12 g / cm 3 .
9. The hard carbon material according to claim 1, characterized in that D v 50 is 1.6~18.0μm, D v 90 is 4.2~35.0μm.
10. The hard carbon material according to any one of claims 1 to 3, 5, 8 to 9, characterized in that: The compacted density of the hard carbon material is 0.90-1.02 g / cm 3 .
11. A secondary battery, characterized in that: It includes a positive electrode plate, a negative electrode plate and an electrolyte, and the negative electrode plate includes a current collector and a negative electrode material attached to at least one surface of the current collector, wherein, The negative electrode material includes the hard carbon material according to any one of claims 1 to 10.
12. An electrical device, characterized in that: It includes: The secondary battery according to claim 11.
Citation Information
Patent Citations
Negative electrode material and preparation method thereof, negative electrode plate, secondary battery and electric equipment
CN116805676A
Negative pole piece, preparation method thereof and low-temperature lithium iron phosphate battery
CN117712280A
Negative electrode hard carbon material, preparation method thereof, negative electrode composition, sodium ion secondary battery and application
CN117810447A
Rolling bearing
JP2005090549A
Negative electrode material for lithium ion secondary battery, method for manufacturing same, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
US20130302675A1